SELECTION OF AIRCRAFT CONFLICT-FREE TRAJECTORIES USING DIFFERENT CONVOLUTIONS OF VECTOR OPTIMALITY CRITERION - Bo, Wang; Kharchenko, Volodymyr; Vasyliev, Denys (Proceedings of National Aviation University (archive), 2015)
The multi-objective decision-making problem of conflict-free flight trajectories selection is solved using linear, multiplicative and Germeier’s convolution of vector optimality criterion, which contains the flight regularity, economy and maneuvers complexity criteria. The computer simulation of multi-objective selection of conflict-free trajectories for resolution of the typical conflict was performed.